The importance of the humanities in the comprehensive professional development of the student - Casquier Ortiz, Jesús R. (2024)
This article presents a critique of the way in which the training of university students is currently approached. The crisis that the humanities are going through in vocational training in these times is pointed out while at the same time it seeks to highlight the importance and value of these for the comprehensive training of students. Through ethical reflection and guided by the question: What is a human being? It was elaborated the need to respond to the social and professional challenges proposed by the reality of the globalized world in which we live scientific and humanistic knowledge.